1999
DOI: 10.1002/(sici)1099-0518(19991015)37:20<3756::aid-pola3>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

The synthesis and polymerization behavior of bimetallic pyridine diamide complexes containing transition metal (Ti, Zr)

Abstract: Titanium and zirconium complexes with a pyridine diamide ligand, [2,6‐(RNCH2)2NC5H3]2− (PDMP; R = 2,6‐dimethylphenyl) have been synthesized and their catalytic behaviors investigated for ethylene polymerization. It was found that the zirconium complexes, [PDMP]ZrCl2 (7) and [PDMP][ZrCl3 × THF]2 (8), gave higher activities than the titanium complexes, [PDMP]TiCl2 (5) and [PDMP][TiCl3]2 (6). The bimetallic complexes (6, 8) gave higher activities than the corresponding monometallic complexes (5, 7). The titanium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…( and, thus, mimics the coordination of the ferrocene-diamide ligand. Complexes of Ti(IV), [25][26][27] Zr(IV), [28][29][30][31] Ta(V), 32,33 lanthanides, [34][35][36] and Th(IV) 37,38 supported by pyridinediamide ligands have been known. Herein we report the synthesis of yttrium and lutetium benzyl complexes bearing NN py and their reactivity toward aromatic N-heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…( and, thus, mimics the coordination of the ferrocene-diamide ligand. Complexes of Ti(IV), [25][26][27] Zr(IV), [28][29][30][31] Ta(V), 32,33 lanthanides, [34][35][36] and Th(IV) 37,38 supported by pyridinediamide ligands have been known. Herein we report the synthesis of yttrium and lutetium benzyl complexes bearing NN py and their reactivity toward aromatic N-heterocycles.…”
Section: Introductionmentioning
confidence: 99%
“…10 In order to probe whether the reactivity of 1 fc -U(CH 2 Ph) 2 is unique, 21 we decided to synthesize analogous dibenzyl complexes of a tridentate, dianionic supporting ligand, 2,6bis(2,6-diisopropylanilidomethyl)pyridine (NN py , Chart 1), because its geometry mimics that of NN fc . Complexes of Ti(IV), [22][23][24] Zr(IV), [25][26][27][28] Ta(V), 29,30 and lanthanides [31][32][33] supported by pyridine-diamide ligands are known.…”
mentioning
confidence: 99%
“…Guided modes are characterized by their azimuthal mode number (m) and radial mode number (n) and for normal incidence only hybrid TM-like HE 1n modes are effectively excited in the NW due to the symmetry of the incident light. 36,45 Assuming that the real part of the propagation constant of the mode along NW axial direction approaches zero, the resonant wavelength can be approximated by 42,43,56…”
Section: Simulation Framework and Sparse Single Radius Nw Arraymentioning
confidence: 99%
“…In addition, optical absorption wavelength range for InAs is large due to its lower bandgap. Researchers have worked on GaAs, [32][33][34][35] silicon, [36][37][38] and InP 25,28,[39][40][41][42][43][44][45] NW based solar absorbers but the work on ultra broadband light absorption using InAs NWs is very few. Wu et al 46 investigated the dependence of optical response on the InAs NW geometry and Rahman et al 41 reported wavelength selective absorption in InAs NWs.…”
Section: Introductionmentioning
confidence: 99%